ANALISA PEMBANGUNAN SALURAN TRANSMISI 275 kV ANTARA GI KILIRANJAO DAN GI PAYAKUMBUH - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2017)
Electrical energy is very important role in human life. rapid population growth resulting in increased electricity needs in Indonesia. Based on the current state of power supply capacity of the next few years will not be able to meet the electricity demand in a number of regions in Indonesia. Therefore PLN as a provider of electrical energy as possible to meet those needs. One step is made by planning to build Transmission Line T / L 275 kV substation Kiliranjao - GI Payakumbuh. With the construction of the substation, it is also necessary distribution of electrical energy that is supplying power to a great everincreasing burden on the city through the transmission line (SUTET) 275 kV. In this study will discuss the environmental feasibility study of development of the transmission line T / L 275 kV Kiliranjao - Payakumbuh and substation. Environmental feasibility study is to obtain accurate information in anticipation of environmental problems that arise and will occur as a result of the construction of the transmission T / L 275 kV, which is useful for various parties, such as PT. PLN as the initiator, the Local Government and Communities.